Empowering Environmental Consciousness: Creating High School E-Modules for Sustainable Change - Meilani Tirta Sari; Hartono Hartono; Sri Sumarni (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to develop valid, practical, and effective e-modules in subjects related to environmental change-oriented biology. This study uses the Rowntree development model which consists of three stages, namely: (1) the planning stage; (2) writing preparation; (3) writing and editing stages. In the third stage, the evaluation is carried out by means of a timer evaluation (self-evaluation, expert review, one-to-one, small group and field tests). The subjects of this study were students grade X at a senior high school in Palembang. The data collection methods employed in this study encompassed observation, interviews, walkthroughs, questionnaires, and tests. The average validation score, based on the results of three validators, was 91%, indicating a high level of validity. The practicality test results from the one-to-one evaluation and the small group evaluation yielded a score of 91.3% (very valid) for the one-to-one test and 90.75% for the small group test, placing them in the highly practical category. The effectiveness test yielded an N-gain result of 0.796, indicating a high level of efficacy. Based on the collected results, it can be inferred that the designed E-Module is valid, practical, and effective.